Divergence of responses to variable socio‐sexual environments in laboratory populations of Drosophila melanogaster evolving under altered operational sex ratios. (1st February 2021) - Maggu, Komal; Ahlawat, Neetika; Geeta Arun, Manas; Meena, Abhishek; Prasad, Nagaraj Guru
Abstract: Post‐copulatory sexual selection (PSS) is an important selective force that determines fitness in polyandrous species. PSS can be intense in some cases and can drive the evolution of remarkable ejaculate properties. In males, investment in ejaculate plays an important role in the outcome of PSS. Thus, males are expected to adaptively tailor their ejaculate according to the perceived competition in their vicinity. Plastic responses in ejaculate investment to variation in intrasexual competition are disparate and widespread in males. We investigated the evolution of plasticity in reproductive traits using Drosophila melanogaster populations evolving for more than 150 generations under male‐ or female‐biased sex ratios. When exposed to different numbers of competitors early in their life, males from these two regimes responded differently in terms of their copulation duration and sperm competitive ability. In addition, the effect of this early life experience wore off at different rates in males of male‐biased and female‐biased regimes with increasing time from the removal of competitive cues. Furthermore, our study finds that males change their reproductive strategies depending upon the identity of rival males. Together, our results provide evidence of the evolution of male reproductive investment that depends on socio‐sexual cues experienced early in life.